Part A: Monoclonal antibody formulations: challenges and developments/ Part B: Characterization of an IgG fab fragment in non-aqueous solvent: Isopropyl Alcohol (IPA) - Shah, Kesha (2022)
Part A: Currently there are about 100 antibody formulations available for the treatment of disease, ranging from migraine prevention, multiple sclerosis and leukaemia. This project will review the development of such formulations and how they relate to antibody subclass structure, stability, storage, prevention of aggregation and administration, costs and safety to patients. The review will include comparative advantages and challenges of intravenous and subcutaneous administration and how challenges of delivery of high concentration formulations (including the viscosity problem) are dealt with. This review will be of great value to the newly reforming NCMH Business Centre based at Sutton Bonington which will act as an advisory and scientific Facility for Biopharma companies such as Astra Zeneca, Arecor, Glaxo Smith Kline, Sanofi and specialising in biopolymer therapeutics and vaccines.